PENGARUH PENGGUNAAN METODE PEMBELAJARAN KONTEKSTUAL DALAM PEMBELAJARAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP N 2 PANTI KABUPATEN PASAMAN - Ramayani, Cici; Fatma, Reni (Aksara Public, 2018)
Researchers interested in researching about the influence of the use of contextual learning methods to the skills to write text description of students class VII SMP N 2 Panti Pasaman District. The purpose of this study is to see whether there is influence from the use of contextual learning methods to the students' writing text description skills. This research type is quantitative with experiment method. The population in this study are students of class VII SMP N 2 Panti Pasaman regency registered in 2017/2018. The sample is taken by purposive sampling technique, that is sampling based on certain consideration and purpose. So the group taken is class VII 1 as the experimental class with the number of students 23 people, and class VII 4 as the control class with the number of students 23 people. The instrument of this research in the form of performance test, that is write text description. Technique of data collection is done by giving performance test. Based on the data analysis shows that the skills of writing text description of the seventh grade students of SMP Negeri 2 Panti without using contextual learning method is in enough qualification with an average value of 60.86. The skill of writing description text by using contextual learning method is in qualification more than enough with the average value of 76,08. Based on t-test results obtained that thitung> ttabel is 2.23> 1.68 at the level of real Î± = 0.05 and hypothesis in this study accepted. So it can be concluded that there is a positive influence of the use of contextual teaching methods to the writing skills of the seventh grade students of SMP Negeri 2 Panti.